Roadmap to safety: a single center study of evidence-informed approach to placenta accreta spectrum - Levy, Rachel A.; Diala, Prisca C.; Rothschild, Harriet T.; Correa, Jasmine; Lehrman, Evan; Markley, John C.; Poder, Liina; Rabban, Joseph; Chen, Lee-may; Gras, Jo; Sobhani, Nasim C.; Cassidy, Arianna G.; et al. (Frontiers in Surgery, 2024)
Objective: To assess the impact of an evidence-informed protocol for management of placenta accreta spectrum (PAS). Methods: This was a retrospective cohort study of patients who underwent cesarean hysterectomy (c-hyst) for suspected PAS from 2012 to 2022 at a single tertiary care center. Perioperative outcomes were compared pre- and post-implementation of a standardized Multidisciplinary Approach to the Placenta Service (MAPS) protocol, which incorporates evidence-informed perioperative interventions including preoperative imaging and group case review. Intraoperatively, the MAPS protocol includes placement of ureteral stents, possible placental mapping with ultrasound, and uterine artery embolization by interventional radiology. Patients suspected to have PAS on prenatal imaging who underwent c-hyst were included in the analysis. Primary outcomes were intraoperative complications and postoperative complications. Secondary outcomes were blood loss, need for ICU, and length of stay. Proportions were compared using Fisher’s exact test, and continuous variables were compared used t-tests and Mood’s Median test. Results: There were no differences in baseline demographics between the pre- (n=38) and post-MAPS (n=34) groups. The pre-MAPS group had more placenta previa (95% pre- vs. 74% post-MAPS, p=0.013) and prior cesarean sections (2 prior pre- vs. 1 prior post-MAPS, p=0.012). The post-MAPS group had more severe pathology (PAS Grade 3 8% pre- vs. 47% post-MAPS, p= 0.001). There were fewer intraoperative complications (39% pre- vs.3% post-MAPS, p<0.001), postoperative complications (32% pre- vs.12% post-MAPS, p=0.043), hemorrhages >1L (95% pre- vs.65% post-MAPS, p=0.001), ICU admissions (59% pre- vs.35% post-MAPS, p=0.04) and shorter hospital stays (10 days pre- vs.7 days post-MAPS, p=0.02) in the post-MAPS compared to pre-MAPS patients. Neonatal length of stay was 8 days longer in the post-MAPS group (9 days pre- vs.17 days post-MAPS, p=0.03). Subgroup analyses demonstrated that ureteral stent placement and uterine artery embolization (UAE) may be important steps to reduce complications and ICU admissions. When comparing just those who underwent UAE, patients in the post-MAPS group experienced fewer hemorrhages greater five liters (EBL >5L 43% pre- vs.4% post-MAPS, p=0.007). Conclusion: An evidence-informed approach to management of PAS was associated with decreased complication rate, EBL >1L, ICU admission and length of hospitalization, particularly for patients with severe pathology.